Penerapan Software Simulasi Elektronika Pada Pembelajaran Listrik Dinamis Terhadap Hasil Belajar Fisika Siswa - Aslamiah Rambe (Universitas Muhammadiyah Tapanuli Selatan, 2017)
The problem in this research is the low of student physics learning result, the low of student learning activity caused by several factors, namely the lack of proper learning method used by the teacher in delivering the lesson, so that the students are less active and just listening, which influences the success of a learning process physics.To solve the problem, this research applied the learning method by using Proteus Electronics Simulation Software. This study aims to determine the increase of learning achievement of physics students and also student learning activities using learning media in the form of Software Simulation Electronics Proteus with learning media MicrosoftPower Point. Type of research used is experiment, that is by making experiment class and control class, where the experimental class is all students of class X-4 which amounted to 32 people and control class that is class X-2 which amounted to 32 people, where class experiment using learning media Software Simulation Proteus Electronics and its control class using Microsoft Powerpoint. The result of this research is the increase of student physics learning result and student learning activity, it can be seen from the result of average value of postes of experiment class is equal to 76,2 and result of mean value of postes of control class equal to 65,5. While the experimental class observation is 86,7 and control class is 69,9. And on the first hypothesis test is F (count) of 13.79 and F (table) of 1.98 so F (count)> F (table) so that Ho is rejected and Ha accepted. And on the second hypothesis F (count) of 5.35 and F (table) of 1.97 so F (count)> F (table) so that Ho is rejected and Ha accepted. Thus it can be concluded that there is an increase in student physics learning outcomes and student learning activities by using Proteus Electronics Simulation Software media in the experimental class and learning media in the form of Microsoft Powerpoint in the control class.Keywords: Learning Activity, Learning Outcomes, Dynamic Electricity, Learning Media, Direct Learning, Proteus Electronics Simulation Software ..